Specificity of the stylistic lexis transposition (on the material of texts of the publicistic style) - Тихоненко, Олена Василівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The purpose of the article is the analysis of the transposition of the colloquial style in the modern publicistic. The achievement of the goal is the solution of tasks: to define the transposition nature, functions of the stylistic transposition of the lexis in the author's speech of newspaper materials. The sources of the research are texts of the newspaper. Specificity of the stylistic lexis transposition based on the material of texts of the publicistic style. The role, place, value and functions of the active lexis: jargons, popular speech, "the lowered lexicon", phraseology are analyzed оn the material of modern newspapers in the article. Transpozita emphasize told and allocate an author's newspaper report with figurativeness and emotional coloring in the light of realities of today in the article. The transposition of lexis of the colloquial style in texts of the periodical is analysed. It was revealed that the stylistic transposition is explained by intralingvistic and extralinguistic factors. The general decrease in the publicistic style, the loss of the concept "literary norm", the vulgarization of the publicistic style are observed.